Youth resilience in front of hyperconnectivity during the pandemic in Catalonia - Pozos Pérez, Katia Verónica (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The purpose of this article is to present the results of four discussion groups between young people, experts, and professionals in various fields in Catalonia. Participatory and critical action research was carried out on the issues on which the effects of COVID-19 had a huge impact: 1) Mental health and youth violence; 2) Hyperconnectivity and information overload; 3) Health and climate emergency; 4) Unemployment and youth emancipation. The diversity of effects on youth has been mostly negative, however, there is also evidence of a series of positive effects or resilience by youngsters.